Engagement of the PFC in consolidation and recall of recent spatial memory - Leon, Wanda C. (2010)
The standard model of system consolidation proposes that memories are initially hippocampus dependent and become hippocampus independent over time. Previous studies have demonstrated the involvement of the medial prefrontal cortex (mPFC) in the retrieval of remote memories. The transformations required to make a memory undergo system's consolidation are thought to require synaptic plasticity. In this study, we investigated the participation of the mitogen-activated protein kinase (MAPK)/ERK pathway in acquisition, memory consolidation, and recent memory recall of the Morris water maze (MWM) task using a 1-d training protocol. To this end, bilateral injections of the MEK inhibitor U0126 into the rat mPFC were performed. The injection of the MEK inhibitor in the mPFC did not affect the acquisition of the MWM. However, MEK inhibitor resulted in impairments on recent memory retrieval either when applied at the end of the learning phase (memory consolidation) or prior to the retention test. The results strongly support the concept that recently acquired and consolidated spatial memories require the mPFC, and that local activation of the MAPK/ERK pathway in the mPFC is necessary for the consolidation and recall of recent memories.